2018
DOI: 10.1056/nejmoa1714855
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of High-Flow Oxygen Therapy in Infants with Bronchiolitis

Abstract: BACKGROUNDHigh-flow oxygen therapy through a nasal cannula has been increasingly used in infants with bronchiolitis, despite limited high-quality evidence of its efficacy. The efficacy of high-flow oxygen therapy through a nasal cannula in settings other than intensive care units (ICUs) is unclear. METHODSIn this multicenter, randomized, controlled trial, we assigned infants younger than 12 months of age who had bronchiolitis and a need for supplemental oxygen therapy to receive either high-flow oxygen therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
397
3
25

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 341 publications
(481 citation statements)
references
References 21 publications
20
397
3
25
Order By: Relevance
“…In our subsequent systematic literature search, three further RCTs have been identified involving 1816 participants. Thus, there have now been four RCTs, including 1891 participants, of HFNC in infants with bronchiolitis: three of these studies involved infants treated in EDs and inpatient paediatric wards in Spain, Australia and New Zealand, and one study involved infants treated in paediatric ICUs in France (Table ).…”
Section: Evidence For Hfnc Therapy In Bronchiolitismentioning
confidence: 99%
See 3 more Smart Citations
“…In our subsequent systematic literature search, three further RCTs have been identified involving 1816 participants. Thus, there have now been four RCTs, including 1891 participants, of HFNC in infants with bronchiolitis: three of these studies involved infants treated in EDs and inpatient paediatric wards in Spain, Australia and New Zealand, and one study involved infants treated in paediatric ICUs in France (Table ).…”
Section: Evidence For Hfnc Therapy In Bronchiolitismentioning
confidence: 99%
“…The three studies conducted outside the ICU differed in important areas, and of concern, there was significant variation in the amount of supplemental oxygen entrained with the HFNC as highlighted in Table . Franklin et al . enrolled patients with oxygen saturations <92–94% (depending on individual institution cut‐offs for hypoxia) and used flow rates of 2 L/kg/min.…”
Section: Evidence For Hfnc Therapy In Bronchiolitismentioning
confidence: 99%
See 2 more Smart Citations
“…Franklin et al 1 demonstrated that in patients under the age of 12 months, high-flow oxygen reduced the need for escalation of care compared with those receiving low-flow oxygen and that it has a role as rescue therapy for those not responsive to standard oxygen therapy. This was a large, randomised and multicentre trial involving both tertiary hospital and regional hospitals.…”
Section: Comment(s)mentioning
confidence: 99%